2011
DOI: 10.1074/jbc.m111.279190
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products (AGEs) Induce Apoptosis via a Novel Pathway

Abstract: Advanced glycation end products (AGEs) accumulate in diabetic patients due to high blood glucose levels and cause multiple deleterious effects. In this study, we provide evidence that the AGE increased cell death, one such deleterious effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 43 publications
(41 reference statements)
5
50
0
Order By: Relevance
“…NF-κB in unstimulated cells remains sequestered in the cytoplasm by IκB. Upon stimulation, IκB undergoes phosphorylation and gradually degrades, and NF-κB becomes free and translocated into the nucleus (28).…”
Section: Longistatin Prevents Nf-κb Translocationmentioning
confidence: 99%
“…NF-κB in unstimulated cells remains sequestered in the cytoplasm by IκB. Upon stimulation, IκB undergoes phosphorylation and gradually degrades, and NF-κB becomes free and translocated into the nucleus (28).…”
Section: Longistatin Prevents Nf-κb Translocationmentioning
confidence: 99%
“…55 In vitro DNA binding assays were performed with HeLa cells which were cultured in 60 mm petri dishes overnight and stimulated with 1 nM of tumour necrosis factor (TNF) for 1 h.…”
Section: Experimental Protocols For Mtt Ldh and Dna Binding Assaysmentioning
confidence: 99%
“…From the expression variation of 23 proteins, it can be concluded that in IL6-treated cells there is a decrease in the level of ionized cellular calcium. Some cytokines are known to increase the cellular calcium level, as reported for IL1B (60), INFG (61) and IL8 (62). The protein levels of these three cytokines were actually found repressed by IL6.…”
Section: Discussionmentioning
confidence: 77%